AMBRA1 drives gastric cancer progression through regulation of tumor plasticity - Ye, Liuqi; Lin, Danlei; Zhang, Wen; Chen, Shiji; Zhen, Yumiao; Akkouche, Sara; Liang, Xiaoxu; Chong, Cheong-Meng; Zhong, Hai-Jing (Frontiers in Immunology, 2024)
BackgroundStomach adenocarcinoma (STAD) is an aggressive malignancy characterized by high tumor plasticity and heterogeneity. This study investigates the role of Autophagy and Beclin 1 Regulator 1 (AMBRA1) in regulating tumor plasticity in STAD progression.MethodsCombined with clinical data, the pan-cancer analysis of AMBRA1 was performed to analyze the role of AMBRA1 in STAD. Western blot, Flow Cytometry (FCM) assay, trans-well assay, wound healing assay, MTT, Reactive Oxygen Species (ROS) assay, Reverse Transcription Quantitative Polymerase Chain Reaction (RT-qPCR) and staining were performed to study the effects of AMBRA1 in AGS human gastric cancer cells. An AGS gastric cancer xenograft model was constructed to further verify the role of AMBRA1 in the development of STAD.ResultsAMBRA1 overexpression correlated with poor overall survival in STAD and was positively associated with T cell CD4+ infiltration. High AMBRA1 expression also indicated worse prognosis in patients with high cancer-associated fibroblast infiltration. AMBRA1 depletion suppressed STAD cell proliferation, migration, and invasion in vitro. Mechanistically, AMBRA1 knockdown induced G1/S cell cycle arrest and triggered cellular senescence through epigenetic alterations, including changes in H3K9me3 levels. AMBRA1 inhibition also sensitized STAD cells to chemotherapeutic agents. In vivo studies confirmed the tumor-suppressive effects of AMBRA1 loss, resulting in reduced tumor growth and increased cellular senescence.ConclusionsOur findings uncover an oncogenic role for AMBRA1 in STAD. Targeting AMBRA1 may induce tumor cell senescence, apoptosis, and potentiate anti-tumor immunity, providing a rationale for developing AMBRA1-targeted precision therapies to improve clinical outcomes in STAD patients.